Determinan Yang Mempengaruhi Kinerja Karyawan Pada PT. Jasa Raharja (Persero) Perwakilan Sumatera Utara - Kannia Rizki Nabilla; Ilham Mubaraq Ritonga (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
Talking about improving employee performance, basically lies in the spirit possessed by existing personnel. Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities assigned to him. A competent person is a person who with his skills does the job easily, quickly, intuitively and very rarely or never makes mistakes. Working conditions or work environment are all aspects of physical work, work psychology and work regulations that can affect job satisfaction and the achievement of work productivity. in the research conducted by the researcher with the title that the researchers examined totaling 113 people. Because the population was 113 people, the researchers took 100% of the population at PT. Jasa Raharja in North Sumatra. Thus the use of the entire population without having to draw a sample this study uses a saturated sample. The results of this study indicate that the value of the correlation/relationship R is 0.629 and it is explained that the percentage of the influence of the dependent variable with the coefficient of determination which is the result of the square of R. The above output results obtained a coefficient of determination (R2) of 0.378, meaning the influence of the variable Competence (X1) Responsibility (X2) and Working Conditions (X3) on employee performance (Y) 37.8% while the rest is influenced by other variables